Crisis at the intersection of four countries: healthcare access for displaced persons in the Lake Chad Basin region. Issue 7 (3rd October 2022) - Oginni, Simon Oyewole; Opoku, Maxwell Peprah; Nketsia, William
ABSTRACT: For a decade, the Lake Chad Basin (LCB) region, which is at the intersection of four countries and home to ethnic groups in Cameroon, Chad, Niger and Nigeria, has been occupied by Boko Haram. The lax borders and deprivation in the region contributed to the emergence and expansion of Boko Haram's insurgency. While much is known about the human casualties of the invasion, little is known about the accessibility of healthcare for the displaced persons. This qualitative study adopted Penchansky and Thomas' ([1981]. "The Concept of Access: Definition and Relationship to Consumer Satisfaction." Medical Care 19 (2): 127–140) theory of access as its conceptual framework (with the following components: geographical accessibility, availability, financial accessibility, acceptability and accommodation) to explore the experiences of the displaced persons in the LCB with respect to access to healthcare. One-on-one interviews ( n  = 51) and two focus group discussions ( n  = 16) were conducted with 67 refugees and internally displaced persons recruited from nine host communities in Nigeria and Cameroon, who shared their perceptions of their healthcare access. The displaced persons faced barriers to their access to the healthcare in the LCB. It was found that for each of the components of the theory of access, the study participants encountered barriers to healthcare access. For example, with regard to financial accessibility (affordability), poverty was identified as the main personal barrier to the displaced persons' healthcare access, and with regard to acceptability, it was communication that was reported to be a barrier. The limitations of the study, the recommendations for future research and the implications of the findings are discussed in detail.